Attitudes, hesitancy, concerns, and inconsistencies regarding vaccines reported by parents of preschool children - Jaime Olbrich Neto; Sandra Regina Leite Rosa Olbrich (Sociedade de Pediatria de São Paulo, 2023)
Abstract Objective: This study aimed to assess attitudes, concerns, information and knowledge about vaccines among parents of preschool children attending kindergartens in a city in the interior of São Paulo, Brazil, using a self-administered questionnaire. Methods: Cross-sectional, questionnaire-based study of knowledge and attitudes regarding vaccination among parents of children aged up to 72 months from public and private schools, between 2018 and 2019. Results: Among the 2,528 questionnaires, 1,261 were answered and grouped by respondents' educational level. According to information, 96.6% of the children were up to date with vaccines. The prevalence of vaccine hesitancy was 5.0%. The lower the educational level, the lower was the income, the larger the number of household members, and the greater the lack of knowledge about vaccines. The higher the educational level, the lower was the vaccine hesitancy, and the greater the dissatisfaction with the information received. Conclusions: Generally, parents consider vaccines to be important for preventing diseases and to be safe, with their benefits outweighing the risks. Positive comments were accompanied by doubts, concerns, hesitancy, and inconsistencies. The level of educational attainment makes a difference in the access to information, medical care provided by pediatricians, and the feeling of obligation to vaccinate. Parents have vaccinated and still intend to vaccinate their children, but ensuring adequate levels of vaccination coverage will be a post-pandemic challenge.